Correction: Optical properties and carrier dynamics in Co-doped ZnO nanorods. Issue 2 (21st December 2020) - Sivan, Aswathi K.; Galán-González, Alejandro; Di Mario, Lorenzo; Tappy, Nicolas; Hernández-Ferrer, Javier; Catone, Daniele; Turchini, Stefano; Benito, Ana M.; Maser, Wolfgang K.; Steinvall, Simon Escobar; Fontcuberta i Morral, Anna; Gallant, Andrew; et al.
Abstract : Correction for 'Optical properties and carrier dynamics in Co-doped ZnO nanorods' by Aswathi K. Sivan et al., Nanoscale Adv., 2021, DOI: ; 10.1039/d0na00693a .